2010
DOI: 10.1038/onc.2010.512
|View full text |Cite|
|
Sign up to set email alerts
|

Chromosomal, epigenetic and microRNA-mediated inactivation of LRP1B, a modulator of the extracellular environment of thyroid cancer cells

Abstract: The low-density lipoprotein receptor-related protein (LRP1B), encoding an endocytic LDL-family receptor, is among the 10 most significantly deleted genes across 3312 human cancer specimens. However, currently the apparently crucial role of this lipoprotein receptor in carcinogenesis is not clear. Here we show that LRP1B inactivation (by chromosomal, epigenetic and microRNA (miR)-mediated mechanisms) results in changes to the tumor environment that confer cancer cells an increased growth and invasive capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 54 publications
(59 reference statements)
1
85
0
Order By: Relevance
“…LRP1B is a member of the LDL receptor family and is among the top 10 genes mutated in human cancer (41). Its large size and location near the FRA2F fragile site (53) may contribute to a high mutation rate as a passenger event; however, several observations favor LRP1B being a bona fide driver mutation in human cancer, including a very high frequency of homozygous deletions (54), frequent point mutation in lung cancer (55,56) and melanoma (57), and promoter methylation in esophageal (58), oral (59), thyroid (60), and gastric cancer (45). Although located adjacent to a fragile site, FRA2F is the least sensitive fragile site in the aphidicolin fragility assay and scored highest in a computational measure for homozygous deletion selection pressure (54).…”
Section: Discussionmentioning
confidence: 99%
“…LRP1B is a member of the LDL receptor family and is among the top 10 genes mutated in human cancer (41). Its large size and location near the FRA2F fragile site (53) may contribute to a high mutation rate as a passenger event; however, several observations favor LRP1B being a bona fide driver mutation in human cancer, including a very high frequency of homozygous deletions (54), frequent point mutation in lung cancer (55,56) and melanoma (57), and promoter methylation in esophageal (58), oral (59), thyroid (60), and gastric cancer (45). Although located adjacent to a fragile site, FRA2F is the least sensitive fragile site in the aphidicolin fragility assay and scored highest in a computational measure for homozygous deletion selection pressure (54).…”
Section: Discussionmentioning
confidence: 99%
“…qPCR for human TERT was performed in 28 thyroid samples, 24 tumours and 3 normal tissue specimens. We also included a normal reference that was produced by pooling RNAs from nine samples of normal thyroid tissue 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Our group reported that the LRP1B expression level in UTC was significantly lower than in WDTC, and that such reduced expression was due to mutation and genomic loss of the LRP1B gene [Prazeres et al, 2011]. UTC showed frequent methylation of the promoter region of the gene, leading to loss of LRP1B expression in more than 80% of UTC [Beroukhim et al, 2010;Prazeres et al, 2011;Eloy et al, 2015].…”
Section: Molecular Alterations Associated With Aggressive Variants Ofmentioning
confidence: 95%